Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Tabukan Barito Kuala - Marsinah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The findings are intended to examine the relationship between work motivation and work discipline on employee performance at the Tabukan District Office. A quantitative approach was chosen, with both variables serving as independent variables, while employee performance acted as the dependent variable. All 20 permanent employees were taken as samples through the census method. Data were collected using a closed-ended questionnaire, and the results were analyzed through validity and reliability tests, multiple linear regression, as well as t and F tests using SPSS version 25. The analysis revealed that work motivation had a significant effect on employee performance (t = 2.858; sig = 0.011), and work discipline also showed a significant effect (t = 2.954; sig = 0.009). Overall, both variables simultaneously had a significant influence on employee performance (F = 71.542; sig = 0.000).